Longitudinal monitoring reveals dynamic changes in circulating tumor cells (CTCs) and CTC-associated miRNAs in response to chemotherapy in metastatic colorectal cancer patients. (1st June 2018) - Tan, Karen; Leong, Sai Mun; Kee, Zizheng; Caramat, Patrick Vincent; Teo, James; Blanco, Michael Vito Martin; Koay, Evelyn S.C.; Cheong, Wai Kit; Soh, Thomas I-Peng; Yong, Wei Peng; Pang, Angela
Abstract: We evaluated the changes in CTC count and CTC-associated miRNAs during the course of chemotherapy in patients with metastatic colorectal cancer. Blood samples were collected from 9 metastatic colorectal cancer patients prior to chemotherapy and at every other chemotherapy session during the course of treatment. CTCs were isolated and enumerated using a size-exclusion method (CellSievo, Singapore). CTC-associated miRNAs were isolated using a paper-based, partitioning method, and analyzed using reverse transcription quantitative real-time PCR (MiRXES, Singapore). CTC count trends generally correlated with disease progression defined by radiological measurements and trends in carcinoembryonic antigen (CEA) levels; hence CTC counts may be useful in cases where CEA is not elevated. CTC-associated miRNAs identified were miR-15b, miR-16, miR-19a, miR-21, miR-25, miR-30d, miR-126, miR-185, miR-221, miR-222, and miR-324–5p. The expression of CTC-associated miRNAs did not appear to correlate with CTC count and exhibited inter-individual heterogeneity. This pilot study suggests that analysis of CTC changes during the course of treatment may be useful in monitoring response to therapy in metastatic colorectal cancer. Highlights: We studied changes in colorectal cancer CTCs and miRNAs from CTCs during treatment. CTC counts trends correlated with disease progression by imaging and CEA levels. miRNAs from CTCs showed transient expression and did not correlate with CTC count. CTC counts during treatment may be useful in monitoring response to therapy.